Bulk crystal growth and characterization of semi-organic nonlinear optical crystal tri-diethylammonium hexachlorobismuthate (TDCB)1. Issue 12 (28th March 2015) - Liu, Guangfeng; Liu, Jie; Zheng, Xiaoxin; Liu, Yang; Yuan, Dongsheng; Zhang, Xixia; Gao, Zeliang; Tao, Xutang
<x xml:space="preserve">Abstract</x> A promising NLO crystal of tri-diethylammonium hexachlorobismuthate (TDCB) has been grown on a large scale; thermal and optical properties were measured.